Factors Affecting Green Performance of Food Supply Chain Firms: A Parallel Mediation Model - AlWadi, Belal Mahmoud; Junejo, Ikramuddin; Ejaz, Sarmad; Ejaz, Faisal; Hossain, Md Billal (Ital Publication, 2025)
Objectives: The objective of this study was to examine the impact of organizational green culture (OGC) on green innovation (GI) and sustainable entrepreneurship practices (SEP), which collectively enhance green performance (GP) in Pakistani food chain sector small and medium enterprises (SMEs). This research investigates how green innovation and sustainable entrepreneurship practices mediate each other towards achieving better green performance. Method: The authors chose deductive quantitative research along with Google Forms-based online surveys to gather data from 239 SMEs using convenience sampling. Structural equation modeling through SmartPLS detected all relationship effects between constructs within the research model. Findings: The study confirms that organizational green culture leads to increased GI and SEP, which in turn contributes to enhanced GP, while SEP operates as the essential mediator between OGC and GP in establishing how cultural values become sustainable practices and environmental improvements. The research merges OGC and innovation aspects with sustainability practices and demonstrates their effects on SMEs through empirical research. Novelty: The research uncovers SEP as a key connection between green culture and performance, which provides business solutions for SMEs that want to merge cultural elements with innovative approaches for sustainability. The research explores green entrepreneurship within emerging markets by demonstrating that developing an organizational green culture leads to creative processes that create sustainable outcomes that enhance environmental results. The paper makes an exceptional contribution by examining two distinct mediators: green innovation and sustainable entrepreneurship practices.